Effect of alcohol label designs with different pictorial representations of alcohol content and health warnings on knowledge and understanding of low‐risk drinking guidelines: a randomized controlled trial. (19th January 2021) - Gold, Natalie; Egan, Mark; Londakova, Kristina; Mottershaw, Abigail; Harper, Hugo; Burton, Robyn; Henn, Clive; Smolar, Maria; Walmsley, Matthew; Arambepola, Rohan; Watson, Robin; Bowen, Sarah; et al.
Abstract: Background and aims: The UK low‐risk drinking guidelines (LRDG) recommend not regularly drinking more than 14 units of alcohol per week. We tested the effect of different pictorial representations of alcohol content, some with a health warning, on knowledge of the LRDG and understanding of how many drinks it equates to. Design: Parallel randomized controlled trial. Setting: On‐line, 25 January–1 February 2019. Participants: Participants ( n = 7516) were English, aged over 18 years and drink alcohol. Interventions: The control group saw existing industry‐standard labels; six intervention groups saw designs based on: food labels (serving or serving and container), pictographs (servings or containers), pie charts (servings) or risk gradients. A total of 500 participants ( 70 per condition) saw a health warning under the design. Measurements: Primary outcomes: (i) knowledge: proportion who answered that the LRDG is 14 units; and (ii) understanding: how many servings/containers of beverages one can drink before reaching 14 units (10 questions, average distance from correct answer). Findings: In the control group, 21.5% knew the LRDG; proportions were higher in intervention groups (all P < 0.001). The three best‐performing designs had the LRDG in a separate statement, beneath the pictograph container: 51.1% [adjusted odds ratio (aOR) = 3.74, 95% confidence interval (CI) = 3.08–4.54], pictograph serving 48.8% (aOR = 4.11, 95% CI = 3.39–4.99) and pie‐chart serving, 47.5% (aOR = 3.57, 95% CI = 2.93–4.34). Participants underestimated how many servings they could drink: control mean = −4.64, standard deviation (SD) = 3.43; intervention groups were more accurate (all P < 0.001), best performing was pictograph serving (mean = − 0.93, SD = 3.43). Participants overestimated how many containers they could drink: control mean = 0.09, SD = 1.02; intervention groups overestimated even more (all P < 0.007), worst‐performing was food label serving (mean = 1.10, SD = 1.27). Participants judged the alcohol content of beers more accurately than wine or spirits. The inclusion of a health warning had no statistically significant effect on any measure. Conclusions: Labels with enhanced pictorial representations of alcohol content improved knowledge and understanding of the UK's low‐risk drinking guidelines compared with industry‐standard labels; health warnings did not improve knowledge or understanding of low‐risk drinking guidelines. Designs that improved knowledge most had the low‐risk drinking guidelines in a separate statement located beneath the graphics.